Protection of Bcl-2 by salubrinal - Kessel, David (2006)
The drug salubrinal has been identified as an inhibitor of phosphatases that act on the eukaryotic translation initiation factor 2 subunit (eIF2α). The resulting maintenance of protein phosphorylation results in enhanced protection from the adverse effects of initiators of the unfolded protein response. We found that salubrinal can also interact with the anti-apoptotic protein Bcl-2, inhibiting binding of the non-peptidic antagonist HA14-1 and of a porphycene that can catalyze Bcl-2 photodamage. As a result, salubrinal offers protection from the apoptotic and autophagic effects that can result from loss of Bcl-2 function.